Midgut Malrotation Causing Intermittent Intestinal Obstruction in a Young Adult - Huseyin Kazim Bektasoglu; Ufuk Oguz Idiz; Mustafa Hasbahceci; Erkan Yardimci; Yurdakul Deniz Firat; Oguzhan Karatepe; Mahmut Muslumanoglu (Case Reports in Surgery)
Midgut malrotation is a congenital anomaly of intestinal rotation and fixation that is generally seen in neonatal population. Adult cases are rarely reported. Early diagnosis is crucial to avoid life threatening complications. Here, we present an adulthood case of midgut volvulus as a rare cause of acute abdomen.